Analisis Kesalahan Berbahasa pada Teks Opini dalam Laman web "Kumparan" Edisi Februari 2025 sebagai Sumber Edukasi dan Informasi - Annura Sastri Aurasyifa; Arrahma Qonita Al Arifin; Alya Nur Lailia Rahmah; Sabrina Yasmin Paramita; Agna Septia Ramadhani; Farrah Suryaningtyas; Asep Purwo Yudi Utomo; Septina Sulistyaningrum (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
Language is one of the communication tools used by every individual or group that is very effective and becomes the main tool to strengthen social, cultural, and economic relationships within society. Language errors are a common phenomenon that occur in our lives, both in speech and writing. The purpose of this research is to analyze language errors based on Syntax, including spelling and effective sentences. This data was obtained from opinion pieces found on the Kumparan laman web, February 2025 edition. This opinion text was analyzed using the listen and note technique. After being examined, it was found that there are 14 spelling and punctuation errors, including: a) 4 errors in the use of foreign languages; b) 4 punctuation errors; c) 2 errors in number writing; d) 1 error in capital letter usage; e) 2 errors in pronoun usage. There are also 21 ineffective sentences, including: a) 15 diction selection errors b) 3 instances of insufficient conjunctions and diction; and c) 3 excessive sentences. This result is expected to provide knowledge about syntax, including spelling, word choice, and other types of usage, which can make opinion texts on the kumparan laman web more accurate in their language use, making them easier for the public to understand.